A Companion to Medieval and Renaissance Bologna
1 online resource.
Keywords: Long neglected by scholars, medieval and Renaissance Bologna is now recognized as a center of economic, political-constitutional, legal, and intellectual innovation, as the city that served as the cultural crossroads of Italy. The city's distinctive achievements and its transition from medieval commune to second largest city of the Renaissance Papal State is illuminated by essays that present the work of current historians, many made available in English for the first time, from the broadest possible perspective: from the material city with its porticoes, the conflicts that brought bloodshed and turmoil to its streets, the disputations of masters and students, and to the masterpieces of artists who laid the foundations for Baroque art.